ANALYSIS OF FACTORS INFLUENCING THE CASH WAQF RECEIVING THROUGH FINTECH WAKF (CROWDFUNDING WAQF MODEL) - Ade Fajar Ramdhani; Rahmat Mulyana; Farit Mochamad Afendi (Department Islamic Economics, 2022)
Purpose–This study determines factors that influenced cash waqf receipts through the Urun Dana Waqaf Platform by adopting the Unified Theory of Access and Use of Technology 2 (UTAUT 2) model with Perceived trust and perceived risk variables.Design/methodology/approach– This research employed a quantitative approach. The population used in this study were in Medan with 142 respondents as samples. The data were analyzed using PLS-SEM with UTAUT Model 2 as the construct latent variable.Findings– The results showed that Performance Expectancy (PE), Social Influence (SI), Perceived Trust (PT), Facilitating Conditions (FC), Hedonic Motivation (HM), Habits (HT) affected on Behavioral Intention (BI) and Habits (HT), Behavioral Intention (BI) affected on User Behavior (UB). Meanwhile, Effort Expectancy (EE), Perceived Risk (PR), Price Value (PV) had no effect on Behavioral intention (BI), and Facilitating Conditions (FC) had no effect on User Behavior (UB).Research limitations/Implications–The discussion focuses on analyzing the factors that influence cash waqf receipts through the waqf crowdfunding platform with the UTAUT 2 acceptance model approach. The scope is limited to users of the waqf crowdfunding platform in Medan City area.Originality/value–This study enriches the literature of Islamic FinTech field, especially on the factors that influence cash waqf receipts through the crowdfunding Waqf Model (CWM) by reaffirming the findings of previous studiesKeywords- Cash Waqf, Crowdfunding Waqf, UTAUT 2, PLS-SEM